2020
DOI: 10.1111/jcmm.16136
|View full text |Cite
|
Sign up to set email alerts
|

ADFP promotes cell proliferation in lung adenocarcinoma via Akt phosphorylation

Abstract: Lung cancer is the most frequent malignant tumour with the highest morbidity and mortality rates worldwide. The analysis of GLOBOCAN 2018 data 1 showed that 2.09 million people would be diagnosed with lung cancer in 2018, accounting for 11.6% of the total cancer cases, and the number of deaths would increase to 1.76 million (18.4% of total). Lung cancer causes significant social and economic burdens and has become a serious global public health concern. 2 Lung adenocarcinoma (LAC) is the most common pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The possible interactions of these proteins were analyzed using bioinformatics, and several hub proteins were identified. Among these, we have already verified the expression and function of DHX9 ( Cao et al, 2017 ; Yan et al, 2019 ), ADFP ( Meng et al, 2021 ; Zhang et al, 2014 ), and GALNT2 ( Wang et al, 2021 ) in LUAD in vitro and in vivo models, patient databases and tissue samples. In the present study, we analyzed the role of SPC21 in LUAD progression and evaluated its value as a prognostic indicator and therapeutic target.…”
Section: Introductionmentioning
confidence: 84%
“…The possible interactions of these proteins were analyzed using bioinformatics, and several hub proteins were identified. Among these, we have already verified the expression and function of DHX9 ( Cao et al, 2017 ; Yan et al, 2019 ), ADFP ( Meng et al, 2021 ; Zhang et al, 2014 ), and GALNT2 ( Wang et al, 2021 ) in LUAD in vitro and in vivo models, patient databases and tissue samples. In the present study, we analyzed the role of SPC21 in LUAD progression and evaluated its value as a prognostic indicator and therapeutic target.…”
Section: Introductionmentioning
confidence: 84%
“…A pathological study found that PLIN2-positive lung adenocarcinoma was associated with a worse outcome reflected in overall and disease-free survival [89]. This was supported by basic research indicating that PLIN2 can promote lung adenocarcinoma cell proliferation by increasing the phosphorylation of Akt [90]. Kimberly et al reported that PLIN2 possesses potential in breast cancer subtype differentiation, as high-grade subtypes, namely, Her2-positive and TNBC, have lower expression of this protein [91].…”
Section: Plin2 and Plin3mentioning
confidence: 92%
“…The association between PLIN2 and cancer is extensively documented. PLIN2 has been associated with tumorigenesis and is often considered as a poor prognosis indicator in cancers of the colon [90,91], breast [92,93], prostate [94,95], lung [96,97], bladder [95], kidney [82,[98][99][100][101][102][103][104][105], thyroid [106], gastric [107], and melanoma [108].…”
Section: Perilipinmentioning
confidence: 99%